Perception, Action, and Intrinsic Motivation in Infants' Motor-Skill Development. (October 2021) - Corbetta, Daniela
Perception, action, and intrinsic motivation play an essential role in early development, promoting the creation and refinement of new and more complex forms of behaviors as infants try a range of sensorimotor patterns in their environment. I use the example of infants' reaching to illustrate how goal-directed action emerges from the intersection of seemingly distinct visual and proprioceptive-tactile-motor spaces that form in the early months following birth. The intersection of these two spaces begins with a casual contingent event involving vision and action: when the hand happens to contact a target. This event, which marks the onset of reaching, provides new behavioral value, reinforces the motor action, and intrinsically motivates infants to attempt to reproduce the behavior. Subsequent repeated cycles of perception and action lead to the exploration of a range of motor responses and a progressive alignment of the visual space with the proprioceptive-tactile-motor space, ultimately fostering the selection and refinement of increasingly successful and refined reaching patterns. Extensive hands-on experience in the environment and learning about the immediate outcomes of actions play a critical role in shaping behavioral development.